Pengelolaan Keuangan dan Prosedur Pelaporan Keuangan - Adawiyah, Wiwik Raobiatul; Aji Kusuma Wijaya; Arie Muhamad Akram (PT. Cendekia Sapta Indonesia, 2025)
This community service program aimed to enhance the competencies of vocational high school (SMK) teachers in West Jakarta in preparing financial reports in accordance with Indonesian accounting standards. The program was implemented through intensive training and mentoring on the use of accounting software, covering the accounting cycle, income statements, balance sheets, and cash flow reports. A total of 29 teachers from the West Jakarta Education Training and Development Center (P4 Jakbar) participated in the activities. The evaluation results indicated a significant improvement, with average scores increasing from 45% in the pre-test to 85% in the post-test. The participant satisfaction survey also revealed high levels of approval regarding the training materials, methods, and facilitators. This program effectively strengthened the accounting competencies of SMK teachers and has the potential to be replicated in other regions.